TEACHING SPEAKING BY USING COMMUNICATION GAMES FOR JUNIOR HIGH SCHOOL STUDENTS - Samsul Arifin; Noviana Tri Purwanti (Universitas PGRI Madiun, 2016)
Speaking is the most important skill to learn. Communication Games is one strategy that can be used to teach speaking. Communication Games are activities in the classroom that aim to practice oral communication. The purpose of this study was to determine the use of Communication Games in speaking teaching and the advantages and disadvantages of Communication Games in teaching speaking at the 8th grade at Nguntoronadi 1 Public Middle School in the 2013/2014 academic year. The method in this study is descriptive qualitative. The results of this study: (1) the teaching procedure of speaking with Communication Games was carried out through 3 activities. Opening, the teacher greets students, checks attendance, performs apperception. Core activities, the teacher divides students into groups, the teacher gives themes, students discuss themes, the second group guesses the first group messenger, each group makes paragraphs based on the topics obtained, the teacher helps the students difficulties, each group presents the results of the discussion. Concluding, the teacher reviews and concludes the material. This procedure is based on RPP and theories from Herrell and Jordan (2008: 95) in chapter II. (2) Advantages: Communication Games can increase students' interest in speaking, can improve student achievement in speaking, can help students actively communicate directly. The disadvantage: there are some students who are lackluster and some students are embarrassed when speaking directly.